Significance of Broken μ−τ Symmetry in Correlating δCP, θ13, Lightest Neutrino Mass, and Neutrinoless Double Beta Decay 0νββ - Gayatri Ghosh (Advances in High Energy Physics)
Leptonic CP violating phase δCP in the light neutrino sector and leptogenesis via present matter-antimatter asymmetry of the Universe entails each other. Probing CP violation in light neutrino oscillation is one of the challenging tasks today. The reactor mixing angleθ13measured in reactor experiments, LBL, and DUNE with high precision in neutrino experiments indicates towards the vast dimensions of scope to detect δCP. The correlation between leptonic Dirac CPV phase δCP, reactor mixing angle θ13, lightest neutrino mass m1, and matter-antimatter asymmetry of the Universe within the framework of μ−τ symmetry breaking assuming the type I seesaw dominance is extensively studied here. Here, a SO(10) GUT model with flavor μ−τ symmetry is considered. In this work, the idea is to link baryogenesis through leptogenesis and the hint of CP violation in the neutrino oscillation data to a breaking of the mu-tau symmetry. Small tiny breaking of theμ−τ symmetry allows a large Dirac CP violating phase in neutrino oscillation which in turn is characterized by awareness of measured value of θ13 and to provide a hint towards a better understanding of the experimentally observed near-maximal value ofνμ−ντmixing angleθ23≃π/4. Precise breaking of the μ−τ symmetry is achieved by adding a 120-plet Higgs to the10+12¯6-dimensional representation of Higgs. The estimated three-dimensional density parameter space of the lightest neutrino mass m1, δCP, and reactor mixing angle θ13 is constrained here for the requirement of producing the observed value of baryon asymmetry of the Universe through the mechanism of leptogenesis. Carrying out numerical analysis, the allowed parameter space of m1, δCP, and θ13 is found out which can produce the observed baryon to photon density ratio of the Universe.